Development and verification of the fluid model for organic degradable maize straw seedling raising bowl - Qu, Jingbo; Qi, Xiaopei; Wang, Fuxin; Che, Yuchen; Che, Shaolong; Zhang, Yuqi; Sun, Yong (International Journal of Agricultural and Biological Engineering, 2025)
The annual yield of maize straws is almost exclusively treated by field burning in China. Therefore, exploring the potential utilization value of maize straws is important to further realize modern agriculture in China. Maize straw-based organic degradable seedling bowls, formulated with pig manure and biogas slurry as binding agents, can be utilized for planting seedlings. These seedling bowls serve to supply organic material to the seedlings, thereby aiding in pest prevention and enhancing soil fertility. The vacuum filter suction forming method was proposed to prepare degradable seedling bowls according to its characteristics. Using the theory of fluid flow, drag reduction, and pressure drop control, the fluid model of seedling bowl material in the process of vacuum filtration was established, and the preparation of seedling bowl mold resistance factors was analyzed. The verification test showed that the pressure change interval and the blowing pressure are important factors influencing the formation of the wet body of the seedling bowl. This study provides theoretical support and guidance for the preparation of biodegradable seedling pots. Keywords: degradable seedling bowl, maize straws, resistance factors, fluid model, vacuum suction filter method DOI: 10.25165/j.ijabe.20251801.5879 Citation: Qu J B, Qi X P, Wang F X, Che Y C, Che S L, Zhang Y Q, et al. Development and verification of the fluid model for organic degradable maize straw seedling raising bowl. Int J Agric & Biol Eng, 2025; 18(1): 43–50.